A expansão da educação superior brasileira : o tensionamento entre o público e o privado - Lorenzet, Deloíze (2011)
This dissertation was built starting from the concerns offered by the new setting of higher education in recent decades. Such configuration is strongly marked by neoliberalism and globalization that has been present through characteristics such as efficiency, productivity, competitiveness, state acuamento, commercialization and profitability that marked the expansion of higher education in the Brazilian Scenery. The present research was guided by the following questions: Do Brazilian public policies prioritize public / state or private / commercial conception? Do changes in Brazilian Higher Education grounded in the flexibility, differentiation and diversification include democratization? Do these joints tend to benefit from the economic, market and social or political sphere? From these questions, the objective of this research is to analyze the tension between public and private in the process of expansion of higher education, assuming that it is a social right and that in addition to its expansion is essential to have democratization. Structurally, the dissertation is organized into three chapters: the first deals with the expansion of Brazilian higher education after the 1990s, where besides the context the influence of international organization is described and analyzed how they make our country subservient, as well as focus on the crisis the idea of the university,according to the theorist Boaventura de Sousa Santos, the second chapter makes a comparison between the presidential octênios Fernando Henrique Cardoso and Luiz Inacio Lula da Silva and the policies they gestated for Higher Education, such as Master Plan for State Reform (MARE), the Law of Directives and Bases of National Education, 1996, the National Education Plan 2001, the University for All Program (PROUNI), the Program of Restructuring and Expansion of Federal Universities (MEETING) and the National Conference on Education, 2010, the third chapter focuses on the tension between public and private higher education in Brazil, performing a mapping of the characteristics of inequality and the need to expand democracy, as well the reinterpretation of Gross Domestic Product (GDP) investiment spending on education